Examining the Trust Index Gap between Australia and the Philippines: Evidence from WVS Data - Arapoc, Jefferson (Journal of Applied And Theoretical Social Sciences, 2023)
This study investigates the vast gap between the interpersonal trust index of Australia and the Philippines by evaluating their respective radius and spheres of trust. The study shows that existing determinants—such as socio-demographic characteristics—are not enough to explain the gap in interpersonal trust between Australia and the Philippines. Results suggest the gap between these two countries’ interpersonal trust could stem from differences in localised and generalised trust, people’s confidence towards existing institutions, and perception of how wealth should be distributed.